MODEL KELEMBAGAAN DAN PERENCANAAN PADA KERJASAMA TATA GUNA LAHAN (BANDA ACEH – ACEH BESAR) - Mutia Sofyan; Mirza Irwansyah; Teuku Budi Aulia (Prodi Magister Teknik Sipil Unsyiah, 2020)
The increasing growth of the city of Banda Aceh, the more it requires urban space to grow. The rapid development of the city of Banda Aceh has an impact on the border area of the administration of the Aceh Besar District. Collaboration between regions with Aceh Besar District can be an alternative to address the problem of limited land in Banda Aceh City in addition to regional expansion policies. The aim of the study was to formulate an institutional and planning model for the collaboration between the comprehensive Banda Aceh – Aceh Besar. This research is a descriptive study using a combination research method and spatial synergism analysis approach. Processing data using the AHP (Analytical Hierarchy Process) methodThe results of the research are based on the perceptions of expert respondents in the Banda Aceh and Aceh Besar District areas, in accordance with AHP analysis. It can be concluded that the main cooperation barrier in forming cooperation is regional authority with the form of cooperation chosen to accommodate the cooperation process of Cooperation Agency of Banda Aceh city - Aceh Besar District. The Banda Aceh City - Aceh Besar District cooperation agency is an organization in the form of an institution consisting of representatives from Banda Aceh City and Aceh Besar District. Furthermore, the direction of the development plan for land use cooperation was carried out in three sub-districts of Aceh Besar District, namely Krueng Barona Jaya District, Ingin Jaya District, and Darul Imarah District with three land use classifications, namely, housing, trade and services.